Pengembangan Aplikasi Inventaris Aset Dan Bahan Habis PakaiBerbasis Web Dan Barcode Pada PT Bank BNI Cabang Banjarmasin - Muhammad Seman (Journal Information Technology Trends (JITRENDS), 2025)
The distribution system for assets and consumable supplies at Bank BNI Banjarmasin Branch is still carried out conventionally through written requests submitted by each unit. This manual recording process, which relies on physical logbooks, often leads to problems such as data loss and recording errors. To address these issues, an inventory management application was developed using literature review and observation for data collection, the Waterfall model based on the System Development Life Cycle (SDLC), and Unified Modeling Language (UML) for system design. The developed application centralizes and organizes inventory data for assets and consumable supplies, enabling more efficient management and supporting more accurate decision-making. Testing results indicate that all application functions perform as expected. Future improvements include ensuring a reliable internet connection and developing a mobile version of the application to facilitate approval processes and enable supervisors to monitor inventory requests more efficiently through smartphones.